DESIGN OF MIXTURES WITH PALM OIL FUEL ASH AND ITS INFLUENCE ON THE PHYSICAL-MECHANICAL PROPERTIES OF CONCRETE - Chavarry Vallejos, Carlos Magno; Pereyra Salardi, Enriqueta; Escobar Serrano, Jackeline Carol; Coral Jamanca, Julio Cesar; De la Cruz Dueñas, Gustavo Gregorio; Ccente Pumapillo, Brigith Melina; Guevara Obando, Estephany Yahaira (LACCEI, 2025)
The objective of this article was to determine the optimal percentage of Palm Oil Fuel Ash (POFA) as a partial replacement for cement in order to improve the physical and mechanical properties of concrete. The research used the deductive scientific method, applied orientation, quantitative approach, retrospective data collection instrument, descriptive, explanatory and correlational type, with experimental, longitudinal, prospective and cohort study design (cause-effect). The aim was to improve the workability, axial compressive strength, tensile strength, density and water absorption of concrete. The workability of concrete with different POFA replacements proposes the use of superplasticizers at percentages greater than 1.14% of the weight of the specific weight of cement for mixtures with a water-cement ratio (w/c) of 0.35, maintaining a workable consistency with replacements in intervals of 8% and 12%. The optimal replacement percentage of 20% of POFA, the compressive strength increased by 8.32% and the maximum tensile strength with a replacement of 10%, increased by 16.02%, with respect to the master concrete. The density of the hardened concrete decreased by 3.18% with the incorporation of 30% of POFA, the water absorption with the incorporation of 30% increased by 17.82% and the slump decreased up to 52.63% with respect to the pattern concrete, going from a fluid consistency to plastic or dry.